Borna disease outbreak with high mortality in an alpaca herd in a previously unreported endemic area in Germany. Issue 5 (17th April 2020) - Schulze, Vanessa; Große, Reinhard; Fürstenau, Jenny; Forth, Leonie F.; Ebinger, Arnt; Richter, Madita T.; Tappe, Dennis; Mertsch, Tanja; Klose, Kristin; Schlottau, Kore; Hoffmann, Bernd; Höper, Dirk; et al.
Abstract: Borna disease virus 1 (BoDV‐1) is the causative agent of Borna disease, an often fatal neurologic condition of domestic mammals, including New World camelids, in endemic areas in Central Europe. Recently, BoDV‐1 gained further attention by the confirmation of fatal zoonotic infections in humans. Although Borna disease and BoDV‐1 have been described already over the past decades, comprehensive reports of Borna disease outbreaks in domestic animals employing state‐of‐the‐art diagnostic methods are missing. Here, we report a series of BoDV‐1 infections in a herd of 27 alpacas ( Vicugna paco s) in the federal state of Brandenburg, Germany, which resulted in eleven fatalities (41%) within ten months. Clinical courses ranged from sudden death without previous clinical signs to acute or chronic neurologic disease with death occurring after up to six months. All animals that underwent necropsy exhibited a non‐suppurative encephalitis. In addition, six apparently healthy seropositive individuals were identified within the herd, suggesting subclinical BoDV‐1 infections. In infected animals, BoDV‐1 RNA and antigen were mainly restricted to the central nervous system and the eye, and sporadically detectable in large peripheral nerves and neuronal structures in other tissues. Pest control measures on the farm resulted in the collection of a BoDV‐1‐positive bicoloured white‐toothed shrew ( Crocidura leucodon ), while all other trapped small mammals were negative. A phylogeographic analysis of BoDV‐1 sequences from the alpacas, the shrew and BoDV‐1‐positive equine cases from the same region in Brandenburg revealed a previously unreported endemic area of BoDV‐1 cluster 4 in North‐Western Brandenburg. In conclusion, alpacas appear to be highly susceptible to BoDV‐1 infection and display a highly variable clinical picture ranging from peracute death to subclinical forms. In addition to horses and sheep, they can serve as sensitive sentinels used for the identification of endemic areas.